Leila Luvena Ambalistiarini Roeslan ADL: PERBUDAKAN ANAK BUAH KAPAL (ABK) WARGA NEGARA INDONESIA DI KAPAL LONG XING 629 MENURUT PROTOKOL PALERMO TAHUN 2000 - Leila Luvena Ambalistiarini Roeslan ADL; Andrey Sujatmoko (Faculty of Law, Universitas Trisakti, 2023)
Human rights can be defined as rights inherent in humans that are fundamental and natural that must be upheld, respected and protected. Indonesian crew members also have human rights, in this case, the right to protection and safety at work, including Indonesian crew members who work on foreign fishing vessels. The problem in this article is whether the acts of violence against Indonesian crew members on the Long Xing 629 Ship are slavery practices that fall into the category of human trafficking according to the 2000 Palermo Protocol and how to resolve cases of violence against Indonesian crew members according to the 2000 Palermo Protocol. The research method used in this article is normative juridical, descriptive in nature, using secondary data analyzed qualitatively, and deductive inference. The conclusion of this article is that violence against Indonesian crew members is a practice of modern slavery that is included in the crime of trafficking in persons according to the 2000 Palermo Protocol, because it has fulfilled the three elements of trafficking in persons which include elements: process, method, and purpose. The Brebes District Court which in its decision awarded compensation to four Indonesian crew members in the amount of 12,706 USD.